Sex Dependent Comparative Study of Hematological Parameters and Blood Cell Characteristics of Three Ornamental Teleosts - A, Jothika; Vijay, Anupama; R, Sivalakshmi; M, Madhavi; L, Mohanasundari (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Aquaculture is one of the rapidly increasing food production sectors in the world. Ornamental fish culture also plays a vital role. hematological parameters serve as a tool to indicate the health of the fish. The present research investigated to acquire basic information on the importance of the size of blood cells, morphology, and hematological parameters in teleost fishes of Devil cichlid (Amphilophus labiatus), Black moor (Carassius auratus), and Koi carp (Cyprinus rubrofuscus). Blood samples from the caudal vein of fish were collected. Standard protocols were used to analyze the hematological investigations such as RBC, WBC, PCV, HB, MCV, MCH, and MCHC. The morphological characteristics of the blood cells were examined using a bright field microscope. A diverse variety of blood cell measurements were executed using a stage and an ocular micrometer. The results showed significant differences between the male and female and also between the species. But the lymphocytes of male and female, C. rubrofusus exhibited no significant difference and the blood indices showed a significant difference of (p<0.05). Therefore, the current study provides baseline information on the hematology of A, labiatus, C. auratus, and C. rubrofuscus in the assessment of these species for proper maintenance and welfare.